A Possible Association Between Executive Dysfunction and Frailty in Patients With Neurocognitive Disorders - Bartoli, Massimo; Palermo, Sara; Cipriani, Giuseppina Elena; Amanzio, Martina (Frontiers in Psychology, 2020)
Frailty is an age-related dynamic status, characterised by a reduced resistance to stressors due to the cumulative decline of multiple physiological systems. Several researches have highlighted a relationship between physical frailty and cognitive decline; however, the role of specific cognitive domains has not been deeply clarified yet. Current studies have hypothesised that physical frailty and neuropsychological deficits may share systemic inflammation and increased oxidative stress in different neurodegenerative disorders, such as Alzheimer’s and Parkinson’s disease. However, the role of the executive dysfunction should be investigated in a more detailed way using a multidimensional approach. With this aim, we conducted a review of the literature on the few experimental articles published to discuss the existence of a relationship between frailty and cognitive impairment in neurocognitive disorders, particularly focusing on the domain of executive dysfunction. The data suggest that physical frailty and cognitive decline, especially executive dysfunction, are two aspects strongly linked in mild and major neurocognitive disorders due to Alzheimer's and Parkinson's disease. In light of this, a new framework linking ageing, cognitive decline, and neurodegenerative diseases is needed. In order to analyse the effects that ageing processes have on neural decline and neurocognitive disease, and to identify relevant groups of users and patients, future longitudinal studies should adopt a multidimensional approach, in the field of primary prevention and in the continuum from mild to major neurocognitive disorder.